Financial liberalization and development: a view form emerging economies - Agosín, Manuel; French-Davis, Ricardo (Estudios de Economía, 2016)
This special volume of Estudios de Economía is devoted to issues of international finance in emerging economies. Finance was at the heart of the debt crisis of the 1980s It was also a leading force in the in the Tequila Crisis, and now it has played a crucial role in the present crisis of some countries in South-East and East Asia. In this volume we will leave the papers to speak for themselves. Here we will only present briefly a discussion of some analytical issues, sketch some features of the Airs of Crisis blowing from Asia, and explore some relevant policy lessons emerging from recent events.